Avaliação do crescimeto de diferentes linhagens de Saccharomyces spp. avaliando sua capacidade de consumo de maltose e matotriose e seus respectivos potenciais de floculação mediante diferentes concentrações de calcio e variações de temperatura - Araujo, Bianca Polinari de (2016)
Beer production is carried out in three main stages, preparation of the wort, fermentation and bottling. After fermentation is necessary to perform a filtration process that ultimately causing a big filter waste and beverage own yeast. Given these costs, the flocculation ability of some yeast began to be observed with greater interest to be shown useful in the filtration step, reducing the costs incurred during this process. It is known that flocculation occurs in certain variables such as temperature variation, calcium concentration, alcohol content, pH and agitation. This study aimed to evaluate the influence of temperature and calcium on the flocculation of selected yeast. Therefore, they were chosen and characterized 45 strains of yeast strains obtained from the bank of Bio4 company, of which we evaluated their potential for consumption and growth in media containing maltose and maltotriose separately. After this step, 12 pre-selected yeasts were differentiated in Lagers and Ales for eating melibiose. For evaluation of flocculation, 4 ALE type yeast were subjected to an experimental design which varied the temperature (18 °C, 22 °C, 26 °C) and calcium concentration (2.08 mol/L, 1.66 mol/L, 1.24 mol/L). For Lager yeast, it performed a design which was used lower temperatures (10 °C, 12 °C, 14 °C) and calcium (2.08 mol/L, 1.66 mol/L, 1.24 mol/L ). As a result, it was analyzed flocculation of each of this yeast, classifying them as 90-100% "high" 40-90% "average" and 0-15% "low" or "no flocculates." Of these, ST 20 and COOP12 have a high flocculation rate, while Maracujá and ST.Cruz remained as an average flocculating yeasts.